Radiation sensors based on GaN microwires. (10th April 2018) - Verheij, D; Peres, M; Cardoso, S; Alves, L C; Alves, E; Durand, C; Eymery, J; Lorenz, K
Abstract: GaN microwires were shown to possess promising characteristics as building blocks for radiation resistant particle detectors. They were grown by metal organic vapour phase epitaxy with diameters between 1 and 2 μ m and lengths around 20 μ m. Devices were fabricated by depositing gold contacts at the extremities of the wires using photolithography. The response of these single wire radiation sensors was then studied under irradiation with 2 MeV protons. Severe degradation of the majority of devices only sets in for fluences above protons cm −2 revealing good radiation resistance. During proton irradiation, a clear albeit small current gain was observed with a corresponding decay time below 1 s. Photoconductivity measurements upon irradiation with UV light were carried out before and after the proton irradiation. Despite a relatively low gain, attributed to significant dark currents caused by a high dopant concentration, fast response times of a few seconds were achieved comparable to state-of-the-art GaN nanowire photodetectors. Irradiation and subsequent annealing resulted in an overall improvement of the devices regarding their response to UV radiation. The photocurrent gain increased compared to the values that were obtained prior to the irradiation, without compromising the decay times. The results indicate the possibility of using GaN microwires not only as UV detectors, but also as particle detectors.